Two-photon absorption properties of two-dimensional π-conjugated chromophores: Combined experimental and theoretical study - Ohta, Koji; Yamada, Satoru; Kamada, Kenji; Slepkov, Aaron D.; Hegmann, Frank A.; Tykwinski, Rik; Shirtcliff, Laura D.; Haley, Michael M.; Salek, Pawel; Gel'Mukhanov, Faris; Agren, Hans (Journal of Physical Chemistry A, 2011)
The two-photon absorption (TPA) properties of four TPEB [tetrakis(phenylethynyl)benzene] derivatives (TD, para, ortho, and meta) with different donor/acceptor substitution patterns have been investigated experimentally by the femtosecond open-aperture Z-scan method and theoretically by the time-dependent density-functional theory (TDDFT) method. The four compounds show relatively large TPA cross sections, and the all-donor substituted species (TD) displays the largest TPA cross-section σ = 520 ± 30 GM. On the basis of the calculated electronic structure, TD shows no TPA band in the lower energy region of the spectrum because the transition density is concentrated on particular transitions due to the high symmetry of the molecular structure. The centrosymmetric donor-acceptor TPEB para shows excitations resulting from transitions centered on D-π-D and A-π-A moieties, as well as transition between the D-π-D and A-π-A moieties; this accounts for the broad nature of the TPA bands for this compound. Calculations for two noncentrosymmetric TPEBs (ortho and meta) reveal that the diminished TPA intensities of higher-energy bands result from destructive interference between the dipolar and three-state terms. The molecular orbitals (MOs) of the TPEBs are derivable with linear combinations of the MOs of the two crossing BPEB [bis(phenylethynyl) benzene] derivatives. Overall, the characteristics of the experimental spectra are well-described based on the theoretical analysis. © 2010 American Chemical Society.